Sustaining Calcutta for 150 years – Pulta-Tallah Water Supply System. Issue Volume 172:Issue EH 3(2019:Aug.) (19th August 2019) - Dey, Ayanangshu; Patra, Parthajit
Abstract : Asia's first surface-water based supply system became operational in 1868 to quench the increasing demand of Calcutta, an emerging commercial hub of 19 th century. Though the city was next to River Hooghly, its original supply was framed to draw water from 22 km upstream at Pulta. Raw water was treated and then transferred to Tallah, near the northern fringe of the city, for subsequent distribution by pumping. Thus, the Pulta-Tallah system started operation with 27.3 mld capacity with slow sand filters. Later, a giant 41 million litre overhead reservoir with 29.6 m staging was introduced at Tallah in 1911, the largest in the world. It acted as a balancing reservoir receiving water during off-peak hours, storing, and then supplying during maximum demand, to insulate the pumps against fluctuating downstream demand. There are six transmission mains transferring water from Pulta to Tallah. Now, this water system has an installed capacity of 1, 182 mld and employs advanced treatment technologies. This paper summarises the history of inception and progressive development of Pulta-Tallah system, which still serves more than half of Calcutta and stands out as an epitome of sustainable urban supply system.